Edukasi Konservasi Air Pada Siswa Di Madrasah Aliyah Darel Hikmah Pekanbaru - Gustiana, Etry; Hardianti, Sri; Agnesia, Yoana (COVIT (Community Service of Tambusai), 2023)
The implementation method used in this activity is in the form of education about Water Conservation and discussions with participants. This activity took place in the Madrasah Aliyah Darel Hikmah Hall on August 6 2023. The targets of this activity were Madrasah Aliyah Darel Hikmah students who lived in the dormitory. The media used to facilitate the implementation of counseling are using infocus and laptops where the counseling material is in the form of Powerpoint, as well as distributing leaflets to the audience. Water conservation is an effort to protect, use and manage water wisely to ensure the availability of sufficient water for current and future needs. Students' education and awareness about water conservation plays an important role in achieving these goals. Good knowledge of the importance of water conservation and appropriate behavior can help students adopt water conservation practices in their daily lives. Schools are formal educational institutions that have roles and responsibilities for children's education. Schools can be shady and ecologically comfortable places. It is important to instill the character of loving the environment and awareness of environmental conservation from an early age, so schools need to implement water conservation.